Estimating herbarium specimen digitization rates: Accounting for human experience. (30th April 2021) - Powell, Caleb; Krakowiak, Alaina; Fuller, Rachel; Rylander, Erica; Gillespie, Emily; Krosnick, Shawn; Ruhfel, Brad; Morris, Ashley B.; Shaw, Joey
Abstract : Premise: Herbaria are invaluable sources for understanding the natural world, and in recent years there has been a concerted effort to digitize these collections. To organize such efforts, a method for estimating the necessary labor is desired. This work analyzes digitization productivity reports of 105 participants from eight herbaria, deriving generalized labor estimates that account for human experience. Methods and Results: Individuals' rates of digitization were grouped based on cumulative time performing each task and then used to estimate a series of generalized labor projection models. In most cases, productivity was shown to improve with experience, suggesting longer technician retention can reduce labor requirements by 20%. Conclusions: Using student labor is a common tactic for digitization efforts, and the resulting outreach exposes future professionals to natural history collections. However, overcoming the learning curve should be considered when estimating the labor necessary to digitize a collection.